THE METAVERSE AND PRIVACY: NEW CRITICAL ISSUES ON THE HORIZON (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The term “metaverse” has become commonly used as a synonym for an immersive, interconnected and interoperable space capable of changing the ordinary distinction between real and virtual. The metaverse is a large and ambitious project, which for the moment does not exist, and which is characterized by innovative features compared to the virtual worlds we know. It can be understood as an interoperable and large-scale network of three-dimensional virtual worlds represented in real time, which can be experienced in a synchronous and unlimited way by a boundless number of users and with continuity of data.326 Interoperability assumes a fundamental importance in the construction of this evolution of the “internet”, and is embodied in the close interconnection between multiple computer systems. Persistence, meanwhile, is the property that allows the metaverse to operate in such a way that it does not need to be paused. This feature will allow operators to create an immersive and constant space where users can carry out any type of activity.327 These preliminary definitions allow us to understand how the metaverse will be the sum of all publicly accessible virtual worlds. The achievement of this new form of reality, which will happen in the near to medium term, introduces new critical issues with regard to the protection of the fundamental rights of users. The right to privacy is certainly among those that are most exposed to the dangers associated with the development of this permanent and immersive infrastructure. Indeed, users will be forced to give up a significant amount of personal data in order to access the metaverse. The potential transposition of many individual activities into this virtual network could affect the essence of the right to privacy and its corollaries.